INSOMNIA AMONG PATIENTS AFTER VIDEO-ASSISTED THORACOSCOPIC LUNG RESECTION AT THE DEPARTMENT OF THORACIC AND VASCULAR SURGERY, BACH MAI HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess insomnia and identify associated factors among patients after video-assisted thoracoscopic lung resection at Bach Mai Hospital in 2025.Methods: A cross-sectional study was conducted on 103 postoperative patients. Insomnia was evaluated on postoperative day 3 using the Insomnia Severity Index (ISI). Sociodemographic characteristics, clinical factors, pain level, psychological status, and environmental influences were also collected.Results: All patients experienced insomnia following surgery. Moderate insomnia accounted for the majority (77.7%), followed by mild (17.4%) and severe insomnia (4.9%). Psychological anxiety, postoperative pain, underlying comorbidities, and environmental factors were significantly associated with postoperative insomnia in this patient group.Conclusion: Insomnia is highly prevalent among patients after video-assisted thoracoscopic lung resection. Early detection and targeted nursing interventions are essential to improve sleep quality and enhance postoperative recovery among this population.
Keywords: insomnia; video-assisted thoracoscopic lung resection; Insomnia Severity Index.